A novel H7N3 reassortant originating from the zoonotic H7N9 highly pathogenic avian influenza viruses that has adapted to ducks. Issue 6 (4th August 2019) - Nakayama, Momoko; Uchida, Yuko; Shibata, Akihiro; Kobayashi, Yoshifumi; Mine, Junki; Takemae, Nobuhiro; Tsunekuni, Ryota; Tanikawa, Taichiro; Harada, Rieko; Osaka, Hiroyuki; Saito, Takehiko
Abstract: The first human case of zoonotic H7N9 avian influenza virus (AIV) infection was reported in March 2013 in China. This virus continues to circulate in poultry in China while mutating to highly pathogenic AIVs (HPAIVs). Through monitoring at airports in Japan, a novel H7N3 reassortant of the zoonotic H7N9 HPAIVs, A/duck/Japan/AQ‐HE30‐1/2018 (HE30‐1), was detected in a poultry meat product illegally brought by a passenger from China into Japan. We analysed the genetic, pathogenic and antigenic characteristics of HE30‐1 by comparing it with previous zoonotic H7N9 AIVs and their reassortants. Phylogenetic analysis of the entire HE30‐1 genomic sequence revealed that it comprised at least three different sources; the HA (H7), PB1, PA, NP, M and NS segments of HE30‐1 were directly derived from H7N9 AIVs, whereas the NA (N3) and PB2 segments of HE30‐1 were unrelated to zoonotic H7N9. Experimental infection revealed that HE30‐1 was lethal in chickens but not in domestic or mallard ducks. HE30‐1 was shed from and replicated in domestic and mallard ducks and chickens, whereas previous zoonotic H7N9 AIVs have not adapted well to ducks. This finding suggests the possibility that HE30‐1 may disseminate to remote area by wild bird migration once it establishes in wild bird population. A haemagglutination‐inhibition assay indicated that antigenic drift has occurred among the reassortants of zoonotic H7N9 AIVs; HE30‐1 showed similar antigenicity to some of those H7N9 AIVs, suggesting it might be prevented by the H5/H7 inactivated vaccine that was introduced in China in 2017. Our study reports the emergence of a new reassortant of zoonotic H7N9 AIVs with novel viral characteristics and warns of the challenge we still face to control the zoonotic H7N9 AIVs and their reassortants.